Research problems in S-2 theses - Rahmadi Nirwanto (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2011)
The study is intended to identify, classify, evaluate, describe, and explain the quality and the patterns of research problems in the S-2 theses of the English Education Program at Islamic University of Malang. Qualitative approach and evaluation designs were used. The data of the study were 135 of S-2 theses of the English Education Program at Islamic University of Malang from 2003-2008. The study reveals that the majority of the research problems, as written in the theses, indicate clarity, researchability, variables being involved, areas, designs, non-factual data or information, and significance.